Pengembangan Lembar Kerja Peserta Didik Zat Pengawet Makanan Berbasis Project Based Learning - Agusta, Riko; Sartika, Rody Putra; Rasmawan, Rahmat (Universitas Batanghari Jambi, 2024)
This study aims to determine the feasibility level and teacher response test and student response test of project-based learning worksheets on food preservatives material developed based on the results of expert judgment and student responses based on the results of field trials. The form of this research is research and development (Research & Development) which adopts the ADDIE development model. The subject of this research is a project-based learning worksheet that was tested on 30 students of SMPN 2 Maya Island. The data collection instruments used were feasibility questionnaire, learner response questionnaire and teacher response questionnaire. The results of data processing show that the student worksheets developed are feasible to use in learning in terms of the percentage of material feasibility, language, and graphics, namely 97.2%; 94.02%; and 94.4%, respectively. The results of the percentage of learner response questionnaires on material aspects, language aspects and graphical aspects. Based on the three aspects of learner response, the percentage of feasibility of project-based learning worksheets on food preservatives is 89.9% which is included in the very high category. The results of the calculation of the percentage of teacher response questionnaires from 3 integrated science subject teachers amounted to 94.98% which is included in the very high category.